Eufemisme dalam Novel Layangan Putus Karya Mommy Asf - Yunda Mardani, Ifra; Asnawi, Asnawi (UIR Press, 2024)
Euphemisms, as a form of softening words to replace taboo language, are an intriguing phenomenon worthy of study. Euphemisms arise in response to the need for more polite expressions in society. The use of euphemisms is not only limited to everyday conversations but is also often found in literary works such as novels. In this study, the focus is on the formation and benefits of euphemisms found in the novel